Assessment of emotional expression in additional language: expression of anger by English-speaking learners of Spanish - Nogueroles López , Marta F.; Doquin de Saint-Preux, Anna (Círculo de Lingüística Aplicada a la Comunicación, 2025)
Expressing and feeling what we say, as well as perceiving the intensity of what we listen are actions that demonstrate linguistic proficiency and communicative efficacy in an additional language. The present study focuses on exploring the capacity for emotional expression of English speakers in Spanish and its assessment by L1 Spanish speakers. In this sense, we intend, firstly, to explore how two B2 level English speakers of Spanish self-perceive their competence and capacity for emotional expression when narrating an angry situation in the target language and, secondly, to examine how 55 L1 Spanish speakers perceive and evaluate the emotional expression of these speakers of Spanish as an additional language (LA). The results of the self-assessment questionnaire show that English speakers, despite their advanced level in Spanish, seem not always to be able to express emotional values in a meaningful way. On the other hand, the results of the questionnaire to L1 Spanish speakers show that English speakers’ assessment of their capacity for emotional expression in Spanish is not particularly focused on linguistic factors, but rather on extra-linguistic aspects.